Drought Impacts on Hydropower Capacity Over the Yangtze River Basin and Their Future Projections under 1.5/2°C Warming Scenarios - Wang, Yu; Li, Huixin; Sun, Bo; Chen, Huopo; Li, Hua; Luo, Yinxue (Frontiers in Earth Science, 2020)
This study aims to reveal the historical and future relationship between droughts in the Yangtze River Basin and hydropower capacity in Zhejiang Province. Generally, the interannual variation of hydropower capacity is positively correlated with the 12-month timescale of the Standardized Precipitation Evapotranspiration Index (SPEI) over the Yangtze River Basin during 1999‒2018, so a more severe drought event in the Yangtze River Basin leads to lower hydropower capacity in Zhejiang Province. Therefore, a linear regression model is constructed based on their year-to-year incremental relationship, which is significant at the 99% confidence level. Using the five global climate models (GCMs) that are good simulations of the interannual variability of precipitation/surface air temperature over the Yangtze River Basin, the results suggest that the severity and the frequency of drought would increase relative to 1999‒2018, with a drought event (SPEI < −0.5) happening once every 2.7 and 2.2 years under 1.5°C and 2.0°C warming scenarios. Based on the interannual incremental relationship between hydropower capacity and SPEI, the hydropower capacity in Zhejiang Province will decrease by 0.34 (1.23) billion kWh under the 1.5°C (2.0°C) warming target when only the meteorological conditions are considered. When the further development of hydropower stations in the future is also considered, the hydropower capacity would increase by −0.28 (1.11) billion kWh under 1.5°C (2.0°C) warming using the logistic growth model. Consequently, the drought events and the development of the hydroelectric system would jointly influence the hydropower capacity in the Yangtze River Basin and the meteorological conditions of a drying trend would contribute to lower hydropower capacity in Zhejiang Province in the future.